2015
DOI: 10.4049/jimmunol.1402321
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Triggered by the Nlrp3 Inflammasome Induces Host Innate Resistance in a Pulmonary Model of Fungal Infection

Abstract: Pathogens are sensed by innate immune receptors that initiate an efficient adaptive immune response upon activation. The elements of the innate immune recognition process for Paracoccidioides brasiliensis include TLR-2, TLR-4, and dectin-1. However, there are additional receptors necessary for the host immune responses to P. brasiliensis. The nucleotide-binding oligomerization domain–like receptor (NLRs), which activate inflammasomes, are candidate receptors that deserve renewed investigation. After pathogen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 63 publications
2
71
1
11
Order By: Relevance
“…Mice and patients infected with P. brasiliensis secrete IL-1β and IL-18, suggesting that NLRP3 is an important player in the recognition of this fungal pathogen (55, 56). The role of NLRP3 using in vivo models of PCM were less explored; however, a recent study using mice systemically infected with P. brasiliensis demonstrated that NLRP3 controls host resistance by inducing a prevalent Th1 immunity associated with IL-18 secretion (40). Because human PCM is acquired by the pulmonary route of infection, in the present study, we sought to characterize the role of NLRP3 inflammasome in i.t.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice and patients infected with P. brasiliensis secrete IL-1β and IL-18, suggesting that NLRP3 is an important player in the recognition of this fungal pathogen (55, 56). The role of NLRP3 using in vivo models of PCM were less explored; however, a recent study using mice systemically infected with P. brasiliensis demonstrated that NLRP3 controls host resistance by inducing a prevalent Th1 immunity associated with IL-18 secretion (40). Because human PCM is acquired by the pulmonary route of infection, in the present study, we sought to characterize the role of NLRP3 inflammasome in i.t.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent work of our lab showed that a dectin-1-Syk mediated mechanism controls NLRP3 inflammasome activation by P. brasiliensis infected macrophages of resistant A/J mice (21). In another study using a murine model of systemic PCM induced by intravenous infection, the susceptibility of NLRP3 and caspase-1 knockout mice to P. brasiliensis infection was evaluated and their increased susceptibility was associated with reduced IL-18 production and Th1 immunity (40). …”
Section: Introductionmentioning
confidence: 99%
“…Adoptive transfer studies in oral candidiasis have shown that NLRP3 primarily functions in myeloid cells, whereas NLRC4 activity is required in stromal cells. Control of Paracoccidiodes braziliensis in the lungs also requires NLRP3 and caspase-1, although infection is regulated more by IL-18 (also processed by inflammasomes) than by IL-1β (Ketelut-Carneiro et al, 2015). …”
Section: Key Cytokines Involved In Antifungal Immunitymentioning
confidence: 99%
“…A recent study has suggested that in addition to LPS, caspase-11 recognizes host-derived oxidized phospholipids, a form of danger-associated molecular pattern that can induce IL-1β release in dendritic cells without triggering pyroptosis (152). Other than A. fumigatus , increased susceptibility of Casp1 −/− Casp11 −/− mice to the fungal pathogens Candida albicans and Paracoccidioides brasiliensis , compared with wild-type mice has also been reported (Table 4) (153156). In macrophages, pyroptosis induced by C. albicans requires the development of fungal hyphae and/or neutralization of the phagosome (157, 158).…”
Section: Introductionmentioning
confidence: 98%